2009
DOI: 10.1002/mnfr.200700486
|View full text |Cite
|
Sign up to set email alerts
|

Influence of postharvest processing and storage on the content of phenolic acids and flavonoids in foods

Abstract: The review is based on the evaluation of electronically collated data published between 2002 to June 2006. It is based on 325 references dealing with the following subclasses of phenolic compounds: hydroxycinnamic and hydroxybenzoic acids, chalcones, flavanones, flavones, flavonols, monomeric flavanols and anthocyanins. Only publications dealing directly with the effects of storage and postharvest processing on the phenolic acid and flavonoid contents of foods were considered. The expectation that the structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
92
0
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(96 citation statements)
references
References 315 publications
(660 reference statements)
0
92
0
4
Order By: Relevance
“…In contrast, Kalt et al (1999) reported that during storage of fresh small fruits such as strawberries and raspberries, anthocyanin content increased. Increase in anthocyanin content during storage may be related to increase in water loss or continued pigment biosynthesis after harvest (Amarowicz et al 2009). However, another factor that caused the difference in anthocyanins content in pomegranate genotypes maybe the variable activity of PAL during senescence; this is the main enzyme to synthesis of phenolic compounds such as anthocyanins (Sakihama et al 2002).…”
Section: −1mentioning
confidence: 99%
“…In contrast, Kalt et al (1999) reported that during storage of fresh small fruits such as strawberries and raspberries, anthocyanin content increased. Increase in anthocyanin content during storage may be related to increase in water loss or continued pigment biosynthesis after harvest (Amarowicz et al 2009). However, another factor that caused the difference in anthocyanins content in pomegranate genotypes maybe the variable activity of PAL during senescence; this is the main enzyme to synthesis of phenolic compounds such as anthocyanins (Sakihama et al 2002).…”
Section: −1mentioning
confidence: 99%
“…Indeed berries, such as strawberries, blueberries, and raspberries, stored at temperatures >15 °C show higher anthocyanins and phenolics contents compared to those stored at lower ones (0 to 6 °C) (Kalt et al, 1999;Cordenunsi et al, 2005). However, other studies have demonstrated that cold storage for up to 3 days leads to relatively small changes in the concentration of different antioxidants in strawberries (Olsson, Ekvall, Gustavsson, & Nilsson, 2004), and that the anthocyanin content of raspberries is not affected by 3 days freezing at 4° C (Amarowicz et al, 2009). (Crupi et al, 2012), that would favor the further cellular biosynthesis of these compounds during postharvest storage.…”
Section: Resultsmentioning
confidence: 98%
“…The storage process can modify the content of phenolic acids and flavonoids in the plant material, leading to an increase or decrease which depend on the storage conditions, such as temperature and time, but also phytochemical stability, and quality of the analyzed food. Generally, a decrease in the polyphenol content with high temperature was shown, but, in other cases, fruit stored at higher temperature has shown higher anthocyanin and flavonoid concentrations and higher antioxidant activity than at lower temperature (Amarowicz et al, 2009;Kalt, Forney, Martin, & Prior, 1999;Shin, Liu, Nock, Holliday, & Watkins, 2007).…”
Section: Introductionmentioning
confidence: 97%
“…This may affect their applications in functional food industry, especially in the light of recent 22 that the effect of storage and technological processing on the content, for most of the polyphenolic classes and subclasses, is negligible in comparison to the differences between the raw materials of different plant species and/or varieties.…”
Section: Resultsmentioning
confidence: 99%